A DNA2 mutation in the ATP-binding motif identified in a diagnostically unresolved individual - Saito, Keisuke; Yatsuka, Yukiko; Kawakami, Ayuno; Kumagaya, Shinichiro; Akiyama, Nana; Okazaki, Yasushi; Murayama, Kei; Ishikita, Hiroshi (Frontiers in Molecular Biosciences, 2025)
Many individuals with chronic, medically unexplained symptoms remain without a diagnosis, despite extensive clinical evaluations. Here, we present a framework integrating genome analysis with protein structural analysis to investigate such a case. Genome sequencing of a diagnostically unresolved individual identified a previously unreported DNA2 missense variant: T652R. This mutation lies within the Walker A motif (GxxxxGKT) of the helicase 1A domain, at an “x” position in the P-loop critical for ATP recognition. Structural analysis revealed that the introduced Arg652 sidechain displaces the conserved Lys654 from its canonical ATP-binding role and forms a new salt bridge with Asp973 in the helicase domain 2A. This interaction likely locks DNA2 in a closed conformation, impairing the dynamic domain movement essential for helicase activity. The case presented here demonstrates how structure-guided analysis of even a single missense variant can provide a basis of understanding the molecular origin of symptoms and help maximize the often underutilized diagnostic potential of genome sequencing.